- A Novel Prognostic Signature Combining Serum Inflammatory Cytokines and Cell-Free Telomere Length in Small Cell Lung Cancer: serum levels of IL-6, IL-8, TNF-α, CRP, and cell-free telomere length (cfTL) - Pan, Mark; Fu, JingYun; Chen, Tao (Journal of Medical Biochemistry, 2026)
Background: Small Cell Lung Cancer (SCLC) remains a lethal malignancy with limited prognostic biomarkers. While systemic inflammation contributes to SCLC progression, the integration of cellular senescence biomarkers with inflammatory markers has not been explored. We hypothesized that combining serum inflammatory cytokines with cell-free telomere length would create a superior prognostic tool.Methods: In this prospective cohort study, 187 extensive-stage SCLC patients were enrolled before first-line chemo-immunotherapy. Baseline serum levels of IL-6, IL-8, TNF-α, CRP, and cell-free telomere length (cfTL) were measured. An Inflamm-Aging Index (IAI) was developed using Cox regression. Primary outcome was overall survival (OS).Results: High IL-6 (HR 2.14, 95% CI 1.45-3.16, p
Keywords: Small cell lung cancer, inflammation, telomere, senescence, biomarkers, prognosis